Impact of Isolated Seed Mycoflora on Seedling Vigour Index of Yardlong Bean Seeds - Rathod, S. A.; Prajapati, V. P. (International Journal of Economic Plants, 2025)
The present investigation was conducted during the year 2022–2023 at the laboratory of Department of Plant Pathology, N.M. College of Agriculture, Navsari Agricultural University, Navsari to isolate seed mycoflora associated with yardlong bean seeds and to study their impact on seedling vigour index. Seed mycoflora was isolated by three different methods viz., agar plate method, standard blotter paper method and deep-freezing method. Pathogenicity tests were conducted under in-vitro and in-vivo conditions and dominant mycoflora were selected to further check their impact on seed health status of yardlong bean seeds. Total ten fungi were isolated viz., Aspergillus niger, A. flavus, Penicillium sp., Rhizopus sp., Fusarium sp., Colletotrichum sp., Curvularia sp., Alternaria sp., Botryodiplodia sp. and Sclerotium sp. Botryodiplodia sp., Curvularia sp., Colletotrichum sp., Fusarium sp. and Sclerotium sp., being dominant, were selected and further used to check their impact on seed germination, shoot length, root length and seedling vigour index of yardlong bean by using paper towel method. Fusarium sp. and Sclerotium sp. showed a considerable decrease in seed germination, root length, shoot length and seedling vigour index of yardlong bean over control.